2011
DOI: 10.1039/c0ja00178c
|View full text |Cite
|
Sign up to set email alerts
|

Protrusions in a painting by Max Beckmann examined with confocal μ-XRF

Abstract: Max Beckmann's ''Pierrette und Clown'' (Pierrette and Clown), 1925, is undoubtedly one of the major works in the collection of the Kunsthalle Mannheim, Germany. In this painting, damages can be seen, described as protrusions. These are blisters and crater-like holes, filled with metallic soap aggregates. Painting samples and cross-sections of the ground layer have been examined by environmental scanning electron microscopy (ESEM) and by confocal synchrotron radiation micro-X-ray fluorescence (CSRmXRF) in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Published analyses of zinc soaps in oil paintings have used primarily FTIR or Raman spectroscopy, often combined with imaging techniques (van der Weerd et al 2003;Keune 2005;Osmond et al 2005Osmond et al , 2012O'Donoghue et al 2006;Faubel et al 2011). Certain of these studies also reported selected results using secondary ion mass spectrometry (SIMS), which has the advantage of spatially resolving components in the zinc soap aggregates.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Published analyses of zinc soaps in oil paintings have used primarily FTIR or Raman spectroscopy, often combined with imaging techniques (van der Weerd et al 2003;Keune 2005;Osmond et al 2005Osmond et al , 2012O'Donoghue et al 2006;Faubel et al 2011). Certain of these studies also reported selected results using secondary ion mass spectrometry (SIMS), which has the advantage of spatially resolving components in the zinc soap aggregates.…”
Section: Introductionmentioning
confidence: 94%
“…While the presence of a certain amount of metallic soaps can help to create a well-dried paint film, high concentrations of zinc soaps have been associated with various types of deterioration in modern oil paintings. Zinc soaps sometimes produce efflorescence or disfiguring protrusions at the surface of paintings (van der Weerd et al 2003;Keune 2005;Osmond et al 2005;O'Donoghue et al 2006;Faubel et al 2011). High concentrations of zinc soaps within the oil paint matrix have also been linked to a lack of cohesion and brittleness in the paint (Rogala et al 2010;Maines et al 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Besides fully exploiting 2D imaging techniques, a few studies have recently explored the third dimension and obtained a full 3D description of soap protrusions (morphology, elemental composition, crystalline phase composition) using state-of-the-art SR based micro-analytical techniques, namely SR micro-tomography (Ferreira et al, 2009), SR confocal μXRF (Faubel et al, 2011) as well as SR 3D μXRD (Vanmeert et al, 2015), respectively.…”
Section: Identification Of Metal Soaps In Paintings: a Dramatic Evolumentioning
confidence: 99%
“…This seems to suggest that zinc white was introduced on Krøyer's palette somewhere between 1886 where he finished the portrait of Christoffer, and 1903 where he begun painting the Drachmann portrait. Zinc white has previously been linked to a number of conservation issues due to the pigment's strong tendency to form zinc carboxylates [13][14][15]. We therefore investigated the formation of zinc soap.…”
Section: Paintingsmentioning
confidence: 99%